Preparation and Characterization of Biochars Obtained from Biomasses for Combustible Briquette Applications - Chaimaa Hadey; M. Allouch; M. Alami; F. Boukhlifi; I. Loulidi (The Scientific World Journal)
Renewable energies have been considered as alternative, clean, available, and ecological sources of energy. The production of biochar from biomass by thermochemical means is considered an efficient method of converting biomass for energy production. In this study, the biochars were produced from the biomasses of peanut shells and sugar cane bagasse at different pyrolysis temperatures (400°C, 450°C, and 500°C). The biomass samples and their produced biochars were characterized using calorific value, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy and energy dispersive X-ray spectrometry (SEM and EDX), compressibility index, and combustion behavior in order to analyze their potential. Experimental results showed that biochar has better fuel qualities compared to raw biomass. We also found that increasing the pyrolysis temperature clearly improved the calorific value, the morphology, the porosity of the biochars as well as the compressibility index of the biochars. The interest of this study was to produce renewable biochar from peanut shell waste and sugar cane bagasse for use as solid fuel.